Mild COVID-19 induces early, quantifiable, persistent troponin I elevations in elder men - Bürgi, Justus J.; Rösslein, Matthias; Nolte, Oliver; Wick, Peter; Garcia Boy, Regine; Stranders, Siegfried; Dollenmaier, Günter; Peier, Karen; Nohynek, Brigitte; Fischer, Aldo; Stolz, Raphael; Cettuzzi, Michele; et al. (Frontiers in Cardiovascular Medicine, 2022)
Importance Elderly patients, especially men, are at risk of increased morbidity from coronavirus disease 2019 (COVID-19). Long-term data on troponin I levels in longitudinal observational studies of outpatients with mild to moderate COVID-19 are scarce. Objective This controlled cohort study aimed to evaluate the course of troponin I concentrations over a long period in convalescent COVID-19 outpatients with mild to moderate symptoms. Setting and participants In this cohort study, individuals with PCR-confirmed, mild to moderate SARS-CoV-2 infection as well as control individuals with confirmed negative PCR and negative SARS-CoV-2 serology were included. Study visits were performed from April 2020 through July 2021 (initialized during the first wave of the corona pandemic in Switzerland). A study visit in patients comprised blood draws every week in the first month and additionally after 8 weeks. This course was repeated in patients observed long-term. Results This study enrolled 278 individuals from the Canton of St. Gallen, Switzerland, aged 12–92 years (59.5% women), who had mild to moderate COVID-19 symptoms (outpatients only) and a diagnosis confirmed by positive RT-PCR. Fifty-four of the participants with confirmed SARS-CoV-2 infection were followed for 14 months with repeat cycles of the testing protocol. In addition, 115 symptomatic patients that were PCR and serology negative were enrolled in the same time period as a control group. In COVID-19 patients, low-level troponin I concentrations (cTnI) were significantly increased from baseline until week 9 after positive RT-PCR diagnosis in men older than 54 years [ΔcTnI = 5.0 ng/L (median); 95% CI 4.1–6.0; p = 0.02]. The troponin I concentration remained elevated throughout 14 months in men older than 54 years within the cohort with a prolonged observation period. This statistically significant change in troponin I concentration was not dependent on co-morbidities in this group. ALT, Creatinine, BNP, and D-Dimer values after convalescence did not differ in comparison to the control cohort. Conclusion In this analysis of individuals with confirmed SARS-CoV-2 infection, hs troponin I levels of men aged 54 or older significantly increased after infection. They remained elevated for at least 14 months after diagnosis. This suggests the possibility of an ongoing, long-term, low-grade myocardial injury. Further studies with focus on elderly patients and a prolonged observational period are necessary to elucidate whether the phenomenon observed is associated with detectable structural changes to the heart muscle or is without further clinical consequences.